Antioxidant activities and inhibitory effects of Mikania micrantha Kunth (Selaput tunggul) against key enzymes involved in hyperlipidemia and hypertension in vitro - Ishak, Amirah Haziyah (2018)
Mikania micrantha Kunth, locally known as „Selaput tunggul‟ in Malaysia, is a plant that traditionally used to reduce the risk of diabetes, hypercholesterolemia, and hypertension. This study was aimed to investigate the antioxidant capacities and inhibitory activities of various extracts of the leaves and stems of M. micrantha on key enzymes related to hyperlipidemia and hypertension in vitro. Total phenolic content (TPC) and total flavonoid content (TFC) were determined using the Folin-Ciocalteu and aluminium chloride colorimetric assays, respectively. The antioxidant capacities were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2‟-azinobis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS), ferric reducing antioxidant power (FRAP), phosphomolybdenum antioxidative power (PAP), and β-carotene bleaching (BCB) assays. The inhibitory activities of M. micrantha on pancreatic lipase (PL), lipoprotein lipase (LPL), HMG-CoA reductase (HMGR), and angiotensin-converting enzyme (ACE) were evaluated in vitro using the spectrophotometric method. In addition, the chemical profiling of the selected extracts was determined using gas chromatography-mass spectrometry (GC-MS). The results demonstrated the ethyl acetate stems (EAS) and leaves (EAL) extracts of M. micrantha had significantly (p < 0.05) greatest TPC (141±0.51 mg gallic acid equivalent/g) and TFC (70.1±0.92 catechin equivalent/g), respectively, compared to samples extracted by other solvents. The EAS extract had also significantly greatest antioxidant capacities using DPPH (EC50=324±61.4 μg/mL), ABTS (0.53±0.01 mmol trolox equivalent/g), FRAP (1.28±0.05 mmol Fe2+/g), PAP (219±7.03 mg ascorbic acid equivalent/g), and BCB (108±2.23%) assays. The ethanol stems (ETS) extract exhibited the highest PL inhibitory activity (IC50=4.49±2.50 μg/mL) followed by hot water leaves (HWL; IC50=4.56±0.07 μg/mL) and ethanol leaves (ETL; IC50=8.02±1.56 μg/mL). These extracts also showed no significant (p > 0.05) difference between each other and orlistat (IC50=0.31±0.01 μg/mL). The ethanol leaves (ETL) extract showed the highest LPL inhibitory activity (IC50=1.42±0.48 μg/mL), however, the difference was found not significant (p > 0.05) between all extracts and orlistat (IC50=1.98±1.22 μg/mL). ETL also showed the highest inhibitory activity against HMG-CoA reductase (50.12±3.44% inhibition), but not significant (p > 0.05) when compared to other extracts except hot water stems (HWS) extract. HWS extract showed the least inhibitory activity against PL, LPL, and HMG-CoA reductase. However, HWS extract showed the greatest ACE inhibition (97.47±1.19%), but not significantly (p > 0.05) different when compared to other extracts and captopril (98.42±0.93%). Overall, all extracts exhibited remarkable inhibitory activity against PL, LPL, HMGR, and ACE. GC-MS analysis of EAL and EAS extracts showed the presence of sesquiterpenes (18.74% and 30.46%, respectively), phenol (14.74% and 16.38%, respectively), and alkane hydrocarbons (26.7% and 10.45%, respectively) which might contribute to its antioxidant and enzyme inhibitory activities. In conclusion, this study indicates the potential of ethyl acetate stems, ethanol leaves, and ethanol stems extracts as antioxidant, anti-hyperlipidemic and anti-hypertensive agents. Results from this study provide baseline knowledge and evidence of the traditional uses of M. micrantha which could be the guidance for future development of nutraceuticals from M. micrantha for hyperlipidemia and hypertension.